Spiritual Healing in the Treatment of Rheumatoid Arthritis: An Exploratory Single Centre, Parallel-Group, Double-Blind, Three-Arm, Randomised, Sham-Controlled Trial. (30th December 2014) - Bliddal, Henning; Christensen, Robin; Højgaard, Lars; Bartels, Else Marie; Ellegaard, Karen; Zachariae, Robert; Danneskiold-Samsøe, Bente
Abstract : Our objective was to investigate the efficacy of "energy/spiritual healing" in rheumatoid arthritis (RA). Eligible patients were women with RA on stable medication. The design was a randomised, blinded, sham-controlled trial; the third group included an external unblinded control of the natural course of RA. Participants in both groups received 8 sessions with "perceived healing" over 21 weeks with 8 weeks of follow-up. Active healing (AH) treatment comprised healing with no physical contact, and sham healing (SH) included exactly the same healing with a sham healer. During intervention, participants wore hearing protectors and were blindfolded. No healing (NH) only had their outcomes assessed. Coprimary outcomes were disease activity score (DAS) for 28 joints and Doppler ultrasound. All 96 patients randomised were handled as the intention-to-treat population, using a baseline-carried forward approach to replace the missing data. Eighty-two (85%) participants completed the 29-week trial. At end point (week 29), mean difference in DAS28 between AH versus SH was statistically but not clinically significant in favour of AH (0.62 DAS28 points; 95% CI: 0.13 to 1.11; P = 0.014 ), while no differences between groups occurred in Doppler ultrasound. There are no clear physiological or psychological explanations for the findings in this tightly controlled study. The trial data indicates a need for independent replication.